PERAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) DALAM MENINGKATKAN KOMITMEN KERJA GURU - Pratiwi, Sella Dwi; Widodo, Widodo; Hidayati, Dian (STKIP Pesisir Selatan, 2025)
Education is the most crucial part of the progress of a nation. In the education component, an educator is called a teacher, an essential profession for implementing the best education. This research aims to describe the role of continuous professional development in increasing teacher work commitment. The method used in this research is descriptive qualitative. The results of this research explain that the role of PKB is essential in increasing teacher work commitment through training, innovative work, and scientific publications. In terms of implementing personal development, teachers who are continuously motivated by the school principal carry out quality improvements independently by participating in independent training, online training, and webinars. Teachers make good contributions through the educational unit environment and the community environment, with parents and fellow teachers in KKG, MGMP, and other teacher organizations. Carrying out innovative work, making scientific work publications, and implementing self-development, which are aspects of Sustainable Professional Development and a form of loyalty of the teachers at the Mulia Medan Private Elementary School, the principal continues to support and motivate teachers to increase their work commitment through developing the teacher's competency.